Respuesta :

[tex](\stackrel{x_1}{-8}~,~\stackrel{y_1}{-8})\qquad (\stackrel{x_2}{-7}~,~\stackrel{y_2}{9}) \\\\\\ \stackrel{slope}{m}\implies \cfrac{\stackrel{rise} {\stackrel{y_2}{9}-\stackrel{y1}{(-8)}}}{\underset{run} {\underset{x_2}{-7}-\underset{x_1}{(-8)}}}\implies \cfrac{9+8}{-7+8}\implies \cfrac{17}{1}\implies 17[/tex]

[tex]\begin{array}{|c|ll} \cline{1-1} \textit{point-slope form}\\ \cline{1-1} \\ y-y_2=m(x-x_2) \\\\ \cline{1-1} \end{array}\implies y-\stackrel{y_2}{9}=\stackrel{m}{17}[x-\stackrel{x_2}{(-7)}]\implies y-9 = 17(x+7)[/tex]